Evaluation of Capitation Scheme as a Financing Instrument for Primary Services in the National Health Insurance (NHI): A Review of Health Economics Literature - Grace Christine; Ayu Anindhita Sekarsari; Budy Irawan; Budi Hartono; Alfani Ghutsa Daud (CV. Inara, 2025)
The study discuss about the capitation scheme is the main financing mechanism for primary healthcare services in the National Health Insurance (NHI), aimed at expanding access, promoting cost efficiency and strengthening promotive and preventive services at First Level Health Facilities (FLHF). This study aims to evaluate performance and effectiveness of capitation schemes as a strategic financing instrument in NHI’s system. Through a narrative- thematic literature review of 20 relevant publications from 2021–2025, this study examines four key aspects: the capitation policy structure, its impact on service quality and coverage, financing efficiency and administrative barriers. The results indicate that while capitation supports financial stability and increases visitation volume, its impact on clinical service quality and promotive-preventive service coverage remains limited. Key barriers include fragmented digital systems (P-Care, SIKDA, e-Kinerja), inadequate managerial capacity and a mismatch between performance indicators and clinical outcomes. This study recommends governance reforms based on output indicators, integration of digital reporting systems, as well as the implementation of a hybrid financing model. Strengthening capitation as a contextual, adaptive and performance-based strategic purchasing instrument is key to sustainable primary service financing within NHI’s framework.